2017
DOI: 10.1002/brb3.800
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Fmr1 results in sex‐specific changes in behavior

Abstract: ObjectiveIn this study, we used a systemic Fmr1 knockout in order to investigate both genotype‐ and sex‐specific differences across multiple measures of sociability, repetitive behaviors, activity levels, anxiety, and fear‐related learning and memory.BackgroundFragile X syndrome is the most common monogenic cause of intellectual disability and autism. Few studies to date have examined sex differences in a mouse model of Fragile X syndrome, though clinical data support the idea of differences in both overall pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
39
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 44 publications
(56 reference statements)
10
39
2
Order By: Relevance
“…The female Fmr1 KO mice used here contain two alleles of the Fmr1 KO, one on each X-chromosome. Male and female Fmr1 KO mice show differences in behavioral measures ( Nolan et al, 2017 ), vocalization production ( Reynolds et al, 2016 ), and neurophysiology ( Giráldez-Pérez et al, 2013 ; Lokanga et al, 2014 ; Scremin et al, 2015 ), but other studies showed similar behaviors between the sexes ( Ding et al, 2014 ). We found that the auditory brainstem phenotypes we observed did not differ between males and females, suggesting predominantly common molecular mechanisms that are not selectively altered by the mutation.…”
Section: Discussionmentioning
confidence: 94%
“…The female Fmr1 KO mice used here contain two alleles of the Fmr1 KO, one on each X-chromosome. Male and female Fmr1 KO mice show differences in behavioral measures ( Nolan et al, 2017 ), vocalization production ( Reynolds et al, 2016 ), and neurophysiology ( Giráldez-Pérez et al, 2013 ; Lokanga et al, 2014 ; Scremin et al, 2015 ), but other studies showed similar behaviors between the sexes ( Ding et al, 2014 ). We found that the auditory brainstem phenotypes we observed did not differ between males and females, suggesting predominantly common molecular mechanisms that are not selectively altered by the mutation.…”
Section: Discussionmentioning
confidence: 94%
“…Fragile X syndrome (FXS) is a neurodevelopmental disorder, caused by a trinucleotide expansion mutation in the FMR1 gene, and is also one of the most prevalent inherited forms of intellectual disability 1 . FXS is often modeled using the Fmr1 knockout (KO) mouse, which can be characterized by several behavioral phenotypes, including alterations in sociability and deficits in fear memory 2 4 . Aside from deficits in spatial and non-spatial learning, one understudied facet of intellectual disability is the ability to incorporate new information into existing learning, termed cognitive flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, impairments have been observed for Fmr1 KO and conditional KO mice in flexibility, learning, and memory, including tasks motivated by either reward or aversion (D'Hooge et al, 1997;Mineur et al, 2002;Ding et al, 2014;Nolan et al, 2017), and those explicitly requiring hippocampal function (Zhao et al, 2005;Guo et al, 2011;Arbab et al, 2018). In general, deficits appear to be significantly milder on the C57BL/6 background strain (Spencer et al, 2011).…”
Section: Discussionmentioning
confidence: 99%